UPAYA PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) BERBANTUAN MEDIA POWER POINT PADA MATA PELAJARAN PENGANTAR EKONOMI DAN BISNIS SISWA SMK NEGERI I BANYUDONO TAHUN AJARAN 2015/2016 - Eka Febrianto; Soetarno Joyoatmojo; Jonet Ariyanto Nugroho (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The objective of research is to improve the learning activeness and learning outcomes in the subject matter of Introduction to Economics and Business of the students in Grade X of Marketing Department of State Vocational High School 1 of Banyudono in Academic Year 2015/2016 through the application of think pair share teaching combined with power point media. This study used the classroom action research (CAR) with two cycles. Each cycle consisted of four phases i.e. planning, implementation, observation, and analysis & reflection. Its subjects were 29 students of the aforementioned school. The data of research were collected through (a) in-depth interview, (b) observation, (c) documentation, and (d) test. The application of the think pair share teaching combined with power point media can improve the learning activeness and learning outcomes in the Introduction to Economics and Business subject matter from Pre-cycle to Cycle I and from Cycle I to Cycle II. The percentage of the students’ learning activeness in visual activities is 13.79% in Pre-cycle, and it becomes 27.59% in Cycle I and 75.86% in Cycle II respectively; the percentage of the students’ learning activeness in oral activities is 0.00% in Pre-cycle, and it becomes 30.79% in Cycle I and 75,86% in Cycle II respectively; the percentage of the students’ learning activeness in writing activities is 0.00% in Pre-cycle, and it becomes 58.62% in Cycle I and 82.76% in Cycle II respectively; the percentage of the students’ learning activeness in mental activities is 0.00% in Pre-cycle, and it becomes 30.90% in Cycle I and 62.07% in Cycle II respectively; the percentage of the students’ learning activeness in emotional activities is 31.00% in Pre-cycle, and it becomes 44.69% in Cycle I and 72.41% in Cycle II respectively. Furthermore, the students’ average score is 73.96 in Pre-cycle, and it becomes 80.73 in Cycle I and 85.28 in Cycle II respectively. Finally, the percentage of the students’ learning completeness is 48.28% in Pre-cycle, and it becomes 65.52% in Cycle I and 86.21% in Cycle II.